Is the Rent Too High? Land Ownership and Monopoly Power - C. Luke Watson; Oren Ziv (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We investigate the sources, scope, and implications of landowner market power. We show how zoning regulations generate spillovers through increased markups and derive conditions under which restricting landownership concentration reduces rents. Using newbuilding-level data from New York City, we find that a 10% increase in ownership concentration in a Census tract is correlated with a 1% increase in rent. Market power is substantial: on average, markups account for nearly a third of rents in Manhattan. Furthermore, pecuniary spillovers between zoning constraints and markups at other buildings are appreciable. Up-zoning that results in 417 additional housing units at zoning-constrained buildings reduces markups on policy-unconstrained units and generates between 5 and 19 additional units through increased competition.
Keywords: R31; R38; L13; 330; monopolistic competition; market power; concentration; rent; housing demand; zoning